Analisis Yuridis Hak Angket Dewan Perwakilan Rakyat Dalam Lingkup Sengketa Pemilu - Dian Ayu Wahyu Nurhidayati; Keisya Oktavia Afida Denna; Najwa Aulia Widyaningrum; Putri Aulia; Rosita Adelia Putri; Theo Galih Prayudha; Kuswan Hadji (Jurnal Relasi Publik, 2024)
Indonesia adheres to a democratic government system that relies on the principle of checks and balances. This principle is inherent in the legislative institution, namely the DPR, which has the right to carry out its duties, one of which is the right to inquiry. In the election context, the right to inquiry can be used to investigate fraud or violations that occur in the election administration process. However, the use of the right to inquiry currently still raises pros and cons among the public. In response to this, this research aims to understand the juridical considerations regarding the right to inquiry in holding elections and analyze the influence of the right to inquiry on elections. The method used in this research is descriptive normative law by studying or reviewing primary and secondary legal materials. This research shows that the DPR’s right to inquiry cannot influence or cancel the election results. However, the DPR’s right to inquiry can be used to request information from the government regarding the implementation of elections.